Analisis Manfaat Aplikasi SakuJapan untuk Pembelajaran Keterampilan Dasar Bahasa Jepang Mahasiswa di Sekolah Vokasi IPB - Bagus Hardika; Mahesa Dzikri Kurniawan; Daffarizqy Prastowiyono; Muhammad Adzka; Humanisa Rubina Lestari (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Language is crucial for human interaction, making foreign language education, especially Japanese, increasingly vital in the global era. Indonesia holds the second-highest number of Japanese learners globally. This study evaluates SakuJapan, a Japanese learning application, to enhance basic Japanese skills among IPB Vocational School students. Using a quantitative descriptive approach with 20 students, data was collected via online questionnaires on usage, features, effectiveness, and motivation. Findings show SakuJapan is an effective and user-friendly tool; 75% of respondents regularly use features like Hiragana, Katakana, vocabulary, and practice questions. The application scored an average effectiveness of 4.3 out of 5, with 85% of users gaining confidence in basic Japanese. While generally well-received, suggestions include offline features, varied exercises, adjustable game difficulty, and more audio, daily conversations, and JLPT-standardized tests. These insights guide further development for a more comprehensive and adaptive learning platform.